Behçet’s Disease - The experience of an Internal Medicine Service - P. Oliveira, Susana (2001)
The authors present a retrospective study onBehçet’s disease, involving 33 patients, observed inan Internal Medicine Service between 1982 and 2000.There were 20 male and 13 female patients. Themean age of first disease manifestation was 24 yearsand the mean age of diagnosis was 32 years. Theclinical manifestations were: oral in 100%, genitalin 84.8%, ocular in 81.8%, articular in 75.7%,cutaneous in 69.6%, central nervous system in27.3%, general in 24.2%, vascular in 21.2%, gastrointestinal in 18.1%, peripheral neuropathy in12.1% and vasculitis in 3% of the observed patients.